1997
DOI: 10.1038/sj.leu.2400714
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of T cell receptor β gene rearrangements and idiotype-reactive T cells in multiple myeloma

Abstract: Clonal T cell populations with idiotype specificity are present to CD3 stimulation which boosts antitumour effector mechin the peripheral blood of a proportion of patients with multiple anisms. 15 It has also been shown that increased numbers of myeloma. We have identified the presence of both T cell subactivated suppressor T cells or NK cells are a good prognostic populations with a specificity for autologous immunoglobin factor at diagnosis. 16,17 fragments and T cell receptor ␤ gene rearrangements in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 5 publications
(6 reference statements)
3
63
0
Order By: Relevance
“…Similarly, in patients with multiple myeloma, the presence of clonal T cells was related to superior prognosis. 52 In accord, long-lasting LGL expansions with clonal TCR ␥/␦ gene rearrangements have been described in a subset of patients receiving an allogeneic stem cell transplant, which were associated with better overall survival, suggesting a graft-versus-leukemia activity. 53,54 We, therefore, speculate that dasatinib treatment reverts the tolerance mechanism and restores the function of unresponsive, exhausted leukemiaspecific cytotoxic cells.…”
Section: Clonal T and Nk Cells In CML Patients 779mentioning
confidence: 69%
“…Similarly, in patients with multiple myeloma, the presence of clonal T cells was related to superior prognosis. 52 In accord, long-lasting LGL expansions with clonal TCR ␥/␦ gene rearrangements have been described in a subset of patients receiving an allogeneic stem cell transplant, which were associated with better overall survival, suggesting a graft-versus-leukemia activity. 53,54 We, therefore, speculate that dasatinib treatment reverts the tolerance mechanism and restores the function of unresponsive, exhausted leukemiaspecific cytotoxic cells.…”
Section: Clonal T and Nk Cells In CML Patients 779mentioning
confidence: 69%
“…On the basis of Southern blot analysis of the TCR␤, which detects monoclonal expansions representing at least 4% to 5% of the total Ficoll-separated peripheral blood cells, 8 our laboratory previously reported on the prognostic significance of true T-cell clonal populations in MM. 9 We found that MM patients exhibiting expanded T-cell clones had a better prognosis than those without detectable clonal bands on Southern blot analysis. 9 Flow cytometric analysis offers the means to isolate and characterize such clones in terms of specificity and function.…”
Section: Introductionmentioning
confidence: 70%
“…9 We found that MM patients exhibiting expanded T-cell clones had a better prognosis than those without detectable clonal bands on Southern blot analysis. 9 Flow cytometric analysis offers the means to isolate and characterize such clones in terms of specificity and function. Previous flow analysis indicated that the expanded T-cell clones, as judged by specific positivity with anti-TCRV ␤ antibodies, expressed the phenotype of cytotoxic T cells and were predominantly CD8 ϩ , CD57 ϩ , CD28 Ϫ , and perforin positive.…”
Section: Introductionmentioning
confidence: 70%
“…TRBV overexpres- sion is more frequently observed in CD4 + T cells than in CD8 + T cells from patients with B-CLL (23), suggesting that leukemic B cells present MHC class II-restricted peptides to CD4 + T cells. Specific T cells from some patients with myeloma can recognize tumor-derived idiotypic immunoglobulin, and patients with these idiotype-reactive T cells are likely to have a better prognosis (26). No change in TRBV usage was detected between T cells that were cultured in a culture medium alone and with phytohemagglutinin stimulation, suggesting that the tumor-associated antigen-mediated selection of monoclonal and oligoclonal TCR families from stimulated T cells were indeed tumor specific (27).…”
Section: Tcr Bias In Diseasementioning
confidence: 85%